Improved conversion of bamboo shoot shells to furfuryl alcohol and furfurylamine by a sequential catalysis with sulfonated graphite and biocatalysts. Issue 66 (6th November 2020) - Feng, Xiao-Qing; Li, Yuan-Yuan; Ma, Cui-Luan; Xia, Yan; He, Yu-Cai
Abstract : Furfurylamine and furfuryl alcohol are known as important furfural-upgrading derivatives in the production of pharmaceuticals, fibers, additives, polymers, etc. Abstract : Furfurylamine and furfuryl alcohol are known as important furfural-upgrading derivatives in the production of pharmaceuticals, fibers, additives, polymers, etc. In a one-pot manner, the catalysis of biomass into furan-based chemicals was established in a tandem reaction with sulfonated Sn–graphite catalysts and biocatalysts. Using a raw bamboo shoot shell (75.0 g L −1 ) as the feedstock, a high furfural yield of 41.1% (based on xylan) was obtained using the heterogeneous Sn–graphite catalyst (3.6 wt% dosage) in water (pH 1.0) for 30 min at 180 °C. Under the optimum bioreaction conditions, the biomass-derived furfural could be transformed into furfuryl alcohol (0.310 g furfuryl alcohol per g xylan in biomass) by a reductase biocatalyst or furfurylamine (0.305 g furfurylamine per g xylan in biomass) using an ω-transaminase biocatalyst. Such one-pot chemoenzymatic processes combined the merits of both heterogeneous catalysts and biocatalysts, and sustainable processes were successfully constructed for synthesizing key bio-based furans.